An Overview of the Cytoskeleton-Associated Role of PDLIM5 - Huang, Xiaolan; Qu, Rongmei; Ouyang, Jun; Zhong, Shizhen; Dai, Jingxing (Frontiers in Physiology, 2020)
Regenerative medicine represented by stem cell technology has become one of the pillar medical technologies for human disease treatment. Cytoskeleton plays important roles in maintaining cell morphology, bearing external forces, and maintaining the effectiveness of cell internal structure, among which cytoskeleton related proteins are involved in and play an indispensable role in the changes of cytoskeleton. PDLIM5 is a cytoskeleton-related protein that, like other cytoskeletal proteins, acts as a binding protein. PDZ and LIM domain 5 (PDLIM5), also known as ENH (Enigma homolog), is a cytoplasmic protein with a molecular mass of about 63 KDa that consists of a PDZ domain at the N-terminus and three LIM domains at the C-terminus. PDLIM5 binds to the cytoskeleton and membrane proteins through its PDZ domain and interacts with various signaling molecules, including protein kinases and transcription factors, through its LIM domain. As a cytoskeleton-related protein, PDLIM5 plays an important role in regulating cell proliferation, differentiation and cell fate decision in multiple tissues and cell types. In this review, we briefly summarize the state of knowledge on the PDLIM5 gene, structural properties, and molecular functional mechanisms of the PDLIM5 protein, and its role in cells, tissues, and organ systems, and describe the possible underlying molecular signaling pathways. In the last part of this review, we will focus on discussing the limitations of existing research and the future prospects of PDLIM5 research in turn.